The National Olympic Committee and Sports Confederation of Denmark (DIF)
The organisations of sport In Denmark the Ministry of Culture is the ministry responsible for sport, because in Denmark both elite sport and sport for all are considered to be an important feature of the cultural landscape. The Danish government, however, interferes very little in sports matters. Danish sport is based on freedom of association and is a very independent and autonomous sector.